Spatial Planning Regulation and Legal Governance for Sustainable Urban Development in Semarang - Anna Yulia Hartati; Ali Martin; Ismiyatun Ismiyatun; Areif Prasetyo (JURNAL AKTA, 2025)
This study examines the implementation of spatial planning regulations and law-based urban governance in Semarang City under the leadership of Hendrar Prihadi, focusing on their impact on urban development, public services, and environmental management. This study answers three main questions: how regulations and spatial planning influence urban development, how law-based governance improves infrastructure, public services, and environmental quality, and what factors support successful implementation. The study uses a descriptive-analytical method with a socio-legal approach, examining policy objectives, regulatory validity, legal principles, norms, and values of justice in urban management, and the implementation of the Smart City concept. Data were obtained from legal documents, government reports, academic studies, and public records to assess the effectiveness of regulations in practice. The results show that consistent implementation of Regional Regulations and Mayoral Regulations, monitored through a web-based monitoring system, ensures high compliance and effective land use control. Integration with the Smart City masterplan supports innovation, service efficiency, and environmental sustainability. the combination of clear regulations, law-based leadership, community participation, and integrated city management creates orderly, inclusive, and sustainable urban development, making Semarang a model for law-based urban governance.